Round herring (genus Etrumeus) contain distinct evolutionary lineages coincident with a biogeographic barrier along Australia’s southern temperate coastline - Di Battista, J.; Randall, J.; Newman, Stephen; Bowen, B. (Springer-Verlag, 2014)
Molecular genetic surveys of marine fishes have revealed that some widely distributed species are actually a composite of multiple evolutionary lineages. This is apparent in the round herrings (genus Etrumeus), wherein a globally distributed taxon (Etrumeus sadina Mitchill 1814) has proven to contain at least seven valid taxa, with more likely awaiting discovery. Here, we survey evolutionary lineages of the nominal E. sadina (formerly E. teres, a junior synonym) across the southern temperate zone of Australia, a marine region divided into three biogeographic provinces based primarily on the distribution of intertidal faunas. Results from morphological and mitochondrial DNA data reveal two evolutionary lineages corresponding to eastern and southwestern provinces (d = 0.007 for cytochrome c oxidase subunit I and d = 0.017 for cytochrome b), possibly initiated by the Bassian Isthmus between Australia and Tasmania during low sea-level stands. The Australian round herring is also genetically distinct from the nearest congeneric forms in the Indian and Pacific Oceans, with a corresponding modal difference in gill-raker counts in most cases. Based on these data, we resurrect the title Etrumeus jacksoniensis for the Australian round herring. While the Bassian Isthmus may have initiated the partition of evolutionary lineages within Australia, additional oceanographic and ecological factors must reinforce this separation in order to maintain diagnostic genetic differences along a continuous temperate coastline.